Принцип справедливости в моральном учении И. Канта - Павлов, Валерий Лукьянович (My University, 2019)
Рассматривается место и роль принципа справедливости в нравственном учении Канта. Обращается внимание на различия в понимании немецким философом роли чувств и разума в формировании идеи справедливости в докритический и критический периоды его творчества. Подчеркивается значение учения И. Канта о самоценности личности при обосновании им принципа справедливости. The article deals with the place and role of the principle of justice in I. Kant’s moral doctrine. Attention is drawn to the differences in understanding by the German philosopher of the role of feelings and reason in shaping the idea of justice in the subcritical and critical periods of his work. Emphasizes the importance of I. Kant’s doctrine on the self-worth of the individual in substantiating the principle of justice.
Keywords: кафедра гуманітарних дисциплін; справедливость; мораль; право; обязанность; критерий; justice; morality; law; duty; criterion